Navigating War Zones: Safeguarding Civilian Rights to Life and Religion through International and Islamic Law - Ashraf, Samina; Nazir, Mahwish (Darul Yasin Al Sys, 2023)
This study explores the protection of civilian rights, focusing on the right to life and religious freedom, within Islamic and international legal contexts. It comprises two main aspects: